Neuroimaging to Assess Neonatal Brain Development and Brain Injury in Neonatal Encephalopathy - Dibble, Megan (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2023)
Neonatal encephalopathy (NE) is a clinical syndrome describing perinatal brain injury and neurological dysfunction in the term-born infant. Magnetic resonance imaging (MRI) is a widely used tool in the assessment of NE, as it provides key information about the pattern and severity of the injury, helps guide treatment decision making, and can be used as a biomarker to predict neurodevelopmental outcome. Diffusion tensor imaging (DTI) is a particularly useful MRI tool, as diffusion abnormalities can be detected in the critical period shortly after birth. Other biomarkers of NE include inflammatory markers and placental pathology, and evidence suggests that these clinical factors may be linked to the pattern of injury seen on MRI in infants with NE. The goal of the present research was to first examine the microstructure of the typically developing neonatal brain, to better understand the effects that adverse neonatal events such as NE have on the brain. Secondly, we aimed to determine if there is an association between placental histology and inflammatory markers, and pattern of brain injury seen on MRI in NE. Finally, we aimed to determine whether these factors can be linked to neurodevelopmental outcome in NE. We first outline typical brain development from conception to adulthood, as well as an overview of neuroimaging methods. We then examine NE in greater detail, and how neuroimaging is used as a tool in NE. We then present four studies ? one systematic review and three empirical studies. The systematic review examines DTI studies in NE and identifies the corpus callosum and posterior limb of the internal capsule as two key white matter tracts that are significantly altered in infants with NE and that are predictive of adverse neurodevelopmental outcomes. Empirical study 1 employs multi-sequence neuroimaging techniques to demonstrate microstructural changes and maturational trajectories of white and grey matter in the brain of the typically developing neonate. We found that DTI, NODDI, and myelin measures were strongly associated with gestational age throughout the brain, but also showed regional variation between metrics, with the strongest associations in the white and deep grey matter. We also identify fALFF as an fMRI measure that is sensitive to gestational age. We show a relationship between MRI metrics and myelination, however, unexpectedly, DTI, NODDI, and myelin measures were not directly associated with fMRI measures. Empirical studies 2 and 3 are retrospective analyses of prospective cohort studies that enrolled infants with NE admitted to the NICU at the National Maternity Hospital, Dublin. Study 2 examined the association between inflammatory markers (EPO, GM-CSF, IL-8, VEGF), placental histology, and MRI brain scores using Barkovich, NICHD NRN and Weeke scoring systems. We identified a positive linear relationship between GM-CSF and MRI brain scores assessed by the Weeke grey matter scoring system, however, no other cytokine or placental associations were found. Study 3 looked at whether the addition of placental histology and inflammatory markers may improve the ability of MRI to predict long-term neurodevelopmental outcome in infants with NE. We found that GM-CSF was predictive of cognitive outcomes (Bayley-III composite scores) when combined with almost all scoring systems: Barkovich, NICHD NRN, Weeke (white matter, cerebellum, and overall, but not grey matter), as well as for normal/abnormal MRI. IL-8 was predictive of both cognitive and motor outcomes when combined with the Weeke grey matter scoring system. No placental associations were found. This thesis provides important information both for MRI researchers and clinicians, into the details of early brain development and injury. We first advocate for the use of multi-sequence MRI techniques to assess the developmental trajectories of structural and functional architecture in the healthy neonatal brain. Secondly, this thesis encourages the use of MRI brain scores and the inflammatory cytokine GM-CSF as a combined biomarker for the assessment of injury and the prediction of cognitive outcome in infants with NE.
APPROVED
Keywords: Neonatal encephalopathy; Diffusion tensor imaging; Functional MRI; Systematic Review